New methodology to assess the potential of solar versus diesel for groundwater irrigation - CGIAR Research Program on Water, Land and Ecosystems (2021)
The methodology was developed in a journal article and reported in a blog, and since then has informed a $50 million World Bank investment in northern Nigeria and forms part of the WLE/IWMI solar online mapping product.